Socioeconomic aspects of human behavioral ecology - Alvard Michael S (Amsterdam Elsevier, 2004)
The volume's papers demonstrate behavioral ecology's maturation as a subfield of anthropology. They demonstrate the breadth of problems that can be gainfully addressed within the paradigm and the richness of specific hypotheses and data that this perspect
Keywords: Human behavior; Social psychology